2017
DOI: 10.1158/1055-9965.epi-17-0211
|View full text |Cite
|
Sign up to set email alerts
|

Quantifying the Genetic Correlation between Multiple Cancer Types

Abstract: Many cancers share specific genetic risk factors including both rare high-penetrance mutations and common single nucleotide polymorphisms (SNPs) identified through genome-wide association studies (GWAS). However, little is known about the overall shared heritability across cancers. Quantifying the extent to which two distinct cancers share genetic origin will give insights to shared biological mechanisms underlying cancer and inform design for future genetic association studies. In this study, we estimated the… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

10
51
2

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 49 publications
(63 citation statements)
references
References 59 publications
10
51
2
Order By: Relevance
“…Several were also similar to array-based heritability estimates from consortia comprised of multiple studies. [4][5][6] For example, our estimate for testicular cancer closely matches the previous family-based estimate of heritability (h 2 =0.25; 95% CI: 0.15-0.37), 3 as well as a previous estimate of array-based heritability (h 2 =0.30; 95% CI: 0.08-0.51). 4 For lung cancer, our estimated heritability of h 2 =0.15 (95% CI: 0.10-0.20) approaches the twin-based estimate of h 2 =0.18 (95% CI: 0.00-0.42), 2 exceeds the array-based estimate from a study using the same methodology (h 2 =0.08; 95% CI: 0.05-0.10), 6 and is comparable to an earlier array-based estimate using individual-level data (h 2 =0.21; 95% CI: 0.14-0.27).…”
Section: Genome-wide Heritability and Genetic Correlationsupporting
confidence: 84%
See 3 more Smart Citations
“…Several were also similar to array-based heritability estimates from consortia comprised of multiple studies. [4][5][6] For example, our estimate for testicular cancer closely matches the previous family-based estimate of heritability (h 2 =0.25; 95% CI: 0.15-0.37), 3 as well as a previous estimate of array-based heritability (h 2 =0.30; 95% CI: 0.08-0.51). 4 For lung cancer, our estimated heritability of h 2 =0.15 (95% CI: 0.10-0.20) approaches the twin-based estimate of h 2 =0.18 (95% CI: 0.00-0.42), 2 exceeds the array-based estimate from a study using the same methodology (h 2 =0.08; 95% CI: 0.05-0.10), 6 and is comparable to an earlier array-based estimate using individual-level data (h 2 =0.21; 95% CI: 0.14-0.27).…”
Section: Genome-wide Heritability and Genetic Correlationsupporting
confidence: 84%
“…1 Efforts toward cancer prevention, screening, and treatment are thus imperative, but they require a more comprehensive understanding of the underpinnings of carcinogenesis than we currently possess. While studies of twins, 2 families, 3 and unrelated populations [4][5][6] have demonstrated substantial heritability and familial clustering for many cancers, the extent to which genetic variation is unique versus shared across different types of cancer remains unclear.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…An ideal approach would consider the effects of body mass index (BMI) and age at menarche, known risk factors for breast cancer that are correlated with lipids. [13][14][15][16][17][18][19] In what follows, we apply the causal inference framework of MR to determine if genetically elevated lipid traits modify breast cancer susceptibility, independent of one another and of BMI and age at menarche. We take advantage of a recent GWAS for lipid levels performed in up to 215,551 individuals of European ancestry 20 to provide power for our causal inference analyses.…”
Section: Introductionmentioning
confidence: 99%